An experimental investigation into the atmospheric degradation of piperazine. (May 2015) - White, Stephen; Angove, Dennys; Azzi, Merched; Tibbett, Anne; Campbell, Ian; Patterson, Michael
Abstract: The atmospheric degradation of piperazine was investigated using an indoor smog chamber. Experiments were carried out in the presence of nitrogen oxides (NOx), ozone or nitric acid. Piperazine reacted rapidly under all evaluated conditions: irradiated in the presence of NOx and with ozone and nitric acid in the dark. Gas phase products from the oxidation of piperazine were identified by infrared spectroscopy, DNPH cartridges followed by HPLC analysis, and by sampling chamber gas through Tenax sorbent material followed by analysis using thermal desorption GC-ITMS (gas chromatography ion trap mass spectrometry). Eight compounds were positively identified, with a further nine compounds tentatively identified using GC–MS based on molecular weight and mass spectra. Ammonia formation was observed from piperazine oxidation, and its formation was from the subsequent reactions of photooxidation products of piperazine rather than directly from the reaction of piperazine. The nitrosamine and nitramine expected from piperazine, N -nitrosopiperazine, and N -nitropiperazine, were both identified and confirmed using 15 NO, with a tentative maximum yield of nitrosamine of less than 5% observed. Aerosol yields, relative to total piperazine reacted not including that which absorbed to the walls, were considerably high but were not able to be quantified absolutely due to unusual behaviour of the scanning mobility particle sizer instrument to aerosol containing amines. The reaction of piperazine with gas phase nitric acid gave rise to immediate formation of aerosol. Highlights: Products from the photooxidation of piperazine in NOx were identified. Nitrosamine and nitramine were positively identified as degradation products. Piperazine reacted rapidly with ozone. High aerosol yields were observed for piperazine degradation scenarios evaluated.